Wanprestasi Dalam Perjanjian Bagi Hasil Perkebunan Pala Di Negeri Morella Maluku Tengah - Mony, Zulfikar; Akyuwen, Rory Jef; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2024)
Law Number 2 of 1960 which regulates Production Sharing Agreements, that: (1) So that the distribution of land results between owners and cultivators is carried out on the basis of justice; (2) By emphasizing the rights and obligations of owners and cultivators to guarantee proper legal status for cultivators, in the agreement on sharing the results of nutmeg plantations in Morella, Central Maluku, where the plantation owner with the initials Fadli Mony and the farmer with the initials Rizki Mony made an agreement in which the owner The plantation makes an agreement with the cultivator to cultivate the nutmeg and the plantation owner promises to share the results of his cultivation, which in the agreement, the plantation owner promises to share 100%, where the plantation owner gets 50% and the cultivator gets 50% but when the cultivator has cultivating nutmeg and it has been sold, it turns out that the plantation owner violated the agreement where the plantation owner only gave 30% to the cultivator who cultivated and sold the nutmeg produce. This research method uses normative research with a legal and conceptual approach as the research methodology. These primary and secondary legal materials are used. Reading and reviewing various types of literature related to the research problem or directly related to the problem being researched is a good technique for collecting and analyzing legal materials in this research. Based on the results of this research, in the case of nutmeg plantation cultivators and plantation owners, they tend to choose deliberation rather than going to court because they prioritize good relations.